Gethok Tular: A Source of Self-Care Knowledge for Older Women with Hypertension in Rural Areas - Rayanti, Rosiana Eva; Werfete, Rivaldy Alfrets; Sasi, Galuh Ambar; Raswandaru, Marsela Riska (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Aims: This study explores the role of gethok tular (oral tradition) in promoting self-care management among elderly Javanese women with hypertension in rural areas, where access to health information remains limited despite existing education programs. Methods: This study employed a qualitative ethnographic approach conducted between January and June 2022. Data were collected through in-depth interviews and observations involving five elderly women in Ngrawan Village, Semarang Regency. To ensure triangulation, additional insights were gathered from midwives and posbindu (integrated healthcare posts for non-communicable diseases) cadres. The participants were Javanese women aged 60 years or older, born and residing in Ngrawan Village, diagnosed with hypertension for more than two years, and actively participating in posbindu activities. Content analysis was used to interpret the data. Results: Gethok tular facilitates the informal exchange of hypertension-related knowledge, particularly during interactions at posbindu sessions. Despite limited understanding of hypertension, participants practiced self-care by staying active, attending check-ups, and using herbal remedies like soursop and avocado leaves to manage symptoms. Conclusion: The gethok tular tradition offers a culturally relevant method for disseminating health information and improving self-care practices in rural communities. This approach holds potential for integration into community-based health programs.